Determinants of maternal deaths amongst mothers who suffered from post-partum haemorrhage: a community-based case control study - Khanna, Divya; Singh, Jai Veer; Agarwal, Monika; Kumar, Vishwajeet (International Journal Of Community Medicine And Public Health, 2018)
Background: The WHO estimates that, of the 529 000 maternal deaths occurring every year 136 000 take place in India amongst which postpartum haemorrhage (PPH) being the most (29.6%) commonly reported complication. However deaths from PPH can be prevented. The purpose of this study was to identify the risk factors contributing to maternal deaths amongst women who develop PPH. Methods: This was a community based paired case-control study done in rural areas of Lucknow, UP (India) done in a period of one year. Thirty-one maternal deaths due to PPH (cases) were matched and compared with two mothers who survived from PPH (controls). Data was analysed using SPSS version 17.0 and Open Epi version 2.3. The appropriate significance test was applied using MacNemar test for paired data. Risk factors obtained significant in bivariate analysis were subjected to conditional multiple logistic regressions for adjustment and controlling the effect of confounding variables. Results have been given in form of unadjusted Odds ratio (UOR) and adjusted Odds ratio (AOR). Results: It was seen that the mothers who had taken ≥4 antenatal visits during the index pregnancy had a protective effect against deaths due to PPH. Home delivery raised the odds of death by seven times. Conclusions: Deaths due to PPH can be reduced by ensuring institutional delivery, good antenatal care and better referral facilities, especially for mothers from weaker sections of society.